Kewenangan Pengadilan Negeri dalam Menetapkan Ketidakhadiran (Afwezigheid) Pemegang Saham Perusahaan Terbuka (Analisis Penetapan Nomor 110/Pdt.P/2025/Pn.Jkt.Pst.) - Gigih Primandiansah; Hendrawarman Hendrawarman (LPPM Iblam School of Law, 2026)
The petition for absence (afwezigheid) in corporate law practice in Indonesia has become an important instrument in resolving obstacles arising from the inactivity of public shareholders in the go-private process. This article analyzes the Central Jakarta District Court's Decision Number 110/Pdt.P/2025/PN.Jkt.Pst. regarding the petition for absence (afwezigheid) filed by PT Onix Capital Tbk. due to the absence of PT Onix Capital Tbk's public shareholders. The study uses a normative juridical method on a court ruling. The results of the study indicate that the court has the authority to provide legal legitimacy for corporations to continue the process from a public company to a private company (going private), by considering evidence of efforts to summon absent public shareholders. This ruling also strengthens the function and authority of the court in ensuring legal certainty while raising new challenges regarding legal protection for minority investors. Based on legal considerations in Decision Number 110/Pdt.P/2025/PN.Jkt.Pst, the Central Jakarta District Court deemed that the application for a determination of absence (afwezigheid) submitted by PT Onix Capital Tbk was a voluntary application within the court's authority and aimed at obtaining legal certainty. The absence of 401 public shareholders was deemed to have fulfilled the elements of afwezigheid as referred to in Article 463 of the Civil Code.